Anaerobic speed reserve and middle-distance performance: A systematic review - del Arco, A.; Martinez Aguirre-Betolaza, A.; Castañeda-Babarro, A. (Strength and Conditioning Journal, 2023)
Anaerobic speed reserve (ASR) allows us to measure an athlete's metabolic and neuromuscular capacities and to profile the different types of middle-distance runners. The main objective of this systematic review was to investigate the relationship between ASR and performance in middle-distance events. Five databases were consulted, and after the screening and selection process, 7 studies were selected. The results show that ASR has no relationship with performance. However, it may do so when one of its variables is equalized or considered as an interaction with its edges. Nonetheless, both maximal sprint speed and maximal aerobic speed influence performance in 800 and 1500 m, with major implications for pacing behavior or tactical decisions.